Development of high-performance pyrimidine nucleoside and oligonucleotide diarylethene photoswitches - Kolmar, Theresa; Büllmann, Simon; Sarter, Christopher; Höfer, Katharina; Jäschke, Andres (Angewandte Chemie, 2021)
Nucleosidic and oligonucleotidic diarylethenes (DAEs) are an emerging class of photochromes with high application potential. However, their further development is hampered by the poor understanding of how the chemical structure modulates the photochromic properties. Here we synthesized 26 systematically varied deoxyuridine- and deoxycytidine-derived DAEs and analyzed reaction quantum yields, composition of the photostationary states, thermal and photochemical stability, and reversibility. This analysis identified two high-performance photoswitches with near-quantitative, fully reversible back-and-forth switching and no detectable thermal or photochemical deterioration. When incorporated into an oligonucleotide with the sequence of a promotor, the nucleotides maintained their photochromism and allowed the modulation of the transcription activity of T7 RNA polymerase with an up to 2.4-fold turn-off factor, demonstrating the potential for optochemical control of biological processes.
Gesehen am 20.04.2023